Literasi Pengenalan Uang kepada Anak-anak di Lingkungan Babakan Gerung - Ni Nyoman Nadi Nuartini; Ni Putu Sasmika Dewi; Sri Rahayu Puspawati; I Komang Widya Purnama Yasa (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The Community Service Program (PkM) is carried out with the aim of improving the understanding of financial literacy in early childhood in the Babakan Gerung Environment. Financial literacy is a basic skill that needs to be instilled from an early age so that children are able to understand the value of money, distinguish needs and wants, and get used to saving from a young age. This activity uses a qualitative descriptive method with three main stages, namely material delivery, educational games, and evaluation. At the stage of delivering the material, children are introduced to various types of money, both metal and paper, along with their functions and nominal values. Furthermore, through shop-shop games, children learn to understand the simple transaction process as well as how to manage money in contextual situations. The evaluation stage is then carried out to assess the level of children's understanding of the material that has been given. The results of the activity showed that there was an increase in children's understanding of the basic concept of money and the importance of financial management. Children look more enthusiastic, actively ask questions, and are able to recognize the value and function of money better. The use of visual aids such as pictures, money, and game media has been shown to be effective in increasing interest in learning. Overall, this program emphasizes the importance of collaboration between formal and non-formal education in building financial literacy awareness from an early age. Through an interactive and fun approach, this activity is expected to foster a wise and independent attitude in managing finances in the future.